Analisis kebutuhan program entrepreneurship bagi santri dhuafa SMP di pondok pesantren - Arie Afriansyah; Akhmad Alim; Ulil Amri Syafri (Al-Liqo: Jurnal Pendidikan Islam, 2026)
This study was motivated by the gap between existing entrepreneurship guidelines and the actual needs of Islamic boarding schools (pesantren) as non-formal educational institutions for underprivileged junior high school students (santri dhuafa). The study aimed to analyze the 2019 Ministry of Education Entrepreneurship Program Guidelines, identify the entrepreneurial needs of students, and provide a foundation for program development. Employing a Research and Development (R&D) approach with the ADDIE model, this article reports the findings of the Analyze phase. Data were collected through interviews, document analysis, and questionnaires administered to 43 santri dhuafa at PP. Tahfiz Al-Muqoddam Karawang and PP. Qoshrul Quran Bogor. The findings indicate that the Ministry’s guidelines require adaptation to the junior high school level, the pesantren context, and the integration of Islamic values. Both institutions lacked structured entrepreneurship programs due to limitations in human resources and capital. The overall level of students’ need for entrepreneurship education reached 77.9% (high category), with the strongest interest in entrepreneurship learning based on Islamic values. These findings highlight the need for a contextual, Islamic values-based, and practice-oriented entrepreneurship program in pesantren.